Team Effectiveness: A Key to Success in ‘IT Organizations’ - Rachna Arora; Sandeep Gajendragadkar; Netra Neelam (Australasian Accounting, Business and Finance Journal, 2023)
This study is an attempt is to examine the relationship between different characteristics which makes project teams effective and lead to the success of projects in IT organizations. A survey was conducted on 110 IT professionals who are part of various project teams in IT organizations. A correlation test is used to see the interdependence, and a linear regression model is used to establish a relationship in team effectiveness variables. The result shows that team purpose and goals, team roles, team processes and team relationships contribute to the team's effectiveness and are interdependent. Team purpose & goals and team relationships are positively related. Team roles are also positively related to team processes. There is a need to build and maintain effective teams to maximize team productivity in the organization. This paper lays emphasis on the necessity of investing efforts in various team effectiveness dimensions, regarding team purpose and goals, team roles, team processes and team relationships for developing effective teams. Teamwork is an important lever to create a competitive edge in a globalized competitive environment, so this study contributes significantly to evaluating characteristics responsible for team effectiveness in IT organizations and would be useful for managers to create effective & resilient teams as workplace resilience has been considered an essential asset for enhancing performance and well-being in the face of challenging circumstances.
Keywords: Efficiency; Effectiveness; Teams; Teamwork; Team processes